Single man and his access to medically assisted reproduction in Greece and in the United Kingdom - Βασιλείου (Marianna Vassiliou) Μαριάννα (Bioethica, 2016)
This paper compares the legal framework in Greece and the United Kingdom on the issue of access to medically assisted reproduction methods - and to the subsequent acquisition of a child - by a single man. Initially, the human right, particularly the right of a single man, to reproduction is presented. At the same time, the reasons for which legal systems explicitly allow access to medically assisted reproduction only to single women are explained. Then, the legal regime governing the method of surrogate motherhood in both countries is exposed, as this is practically the only method by which a single man can procreate. The presentation of the Greek legal framework follows, a framework which excludes single man from access to medically assisted reproduction, as well as the case law which sought to cover the legal vacuum, by applying in a proportional way the relevant provisions for single women. Then, the rules governing the United Kingdom on the question are analyzed, where the case law has bypassed the non-explicit inclusion of single man to the persons entitled to have a child using the methods of medically assisted reproduction. Finally, as a solution to the issue, the combination of the two systems is proposed, as well as an effective and de facto recognition of the right of single men to having a child with the help of technology.